2021
DOI: 10.1101/2020.12.28.20248949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histopathological Profile of Cervical Biopsies in Northern Malawi: A Retrospective Study

Abstract: ObjectivesThis study was carried out to determine the histopathological profile of cervical biopsies in a public tertiary hospital in Mzuzu, northern region of Malawi.SettingA public tertiary hospital in Mzuzu, northern region of MalawiParticipantsThis was a retrospective study of all cervical biopsy specimen reports received in a public tertiary hospital in northern Malawi over a period of 5 years from July 2013-June 2018. Eleven reports which had missing demographic and clinical data or had inconclusive resu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…The nursing EBP implementation in this study was assessed as positive. This has been different from the study of Felor [24], Kaseka [25], and Li [26] which suggested that EBP implementation is poor. EBP for nurses is new, and nurses are not aware of doing research related to care.…”
Section: Discussioncontrasting
confidence: 91%
“…The nursing EBP implementation in this study was assessed as positive. This has been different from the study of Felor [24], Kaseka [25], and Li [26] which suggested that EBP implementation is poor. EBP for nurses is new, and nurses are not aware of doing research related to care.…”
Section: Discussioncontrasting
confidence: 91%
“…Likewise, a nine years retrospective data analysis of 1,049 cervical histology reports in Ghana revealed that the majority of cervical samples at 99.4% were diagnosed as cervical carcinoma [ 27 ]. Another retrospective-based study aimed at analyzing 500 histological reports in Malawi showed that the proportion of cervicitis, endocervical polyp, and CIN to be 46.0%, 20.5%, and 24.4%, respectively [ 33 ]. Further, a study in Nepal on the histological profile of cervical samples indicated that benign, inflammatory, borderline, and malignant lesions were the commonest findings.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent infection with oncogenic or high-risk Human papillomaviruses (HR-HPV; e.g., HPV16, 18,31,33,35,39,45,51,52,56,58,59 and 68) is the main cause of cervical cancer [8]. However, a recent study revealed that nearly 5% of cervical cancer cases were not HPV-associated, which is a unique biological entity with a different molecular profile when compared with HPV-associated cancers [2].…”
Section: Introductionmentioning
confidence: 99%